2014
DOI: 10.1371/journal.pone.0108274
|View full text |Cite
|
Sign up to set email alerts
|

Reading Performance Is Enhanced by Visual Texture Discrimination Training in Chinese-Speaking Children with Developmental Dyslexia

Abstract: BackgroundHigh order cognitive processing and learning, such as reading, interact with lower-level sensory processing and learning. Previous studies have reported that visual perceptual training enlarges visual span and, consequently, improves reading speed in young and old people with amblyopia. Recently, a visual perceptual training study in Chinese-speaking children with dyslexia found that the visual texture discrimination thresholds of these children in visual perceptual training significantly correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…Previous studies have indicated that the visual perceptual processing (e.g., the low-spatial-frequency sensitivity, geometric-figure processing) had an impact on the recognition and encoding processes during Chinese reading in typically developed children and adults (Luo et al, 2013; Yang et al, 2013; Zhao et al, 2013, 2014). Various studies have shown that Chinese individuals with developmental dyslexia exhibit visual deficits (Chung et al, 2008; Wang et al, 2010; Meng et al, 2011; Qian and Bi, 2014), and visual function training for dyslexics can improve their reading-related skills (Meng et al, 2014; Wang et al, 2014; Qian and Bi, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the visual perceptual processing (e.g., the low-spatial-frequency sensitivity, geometric-figure processing) had an impact on the recognition and encoding processes during Chinese reading in typically developed children and adults (Luo et al, 2013; Yang et al, 2013; Zhao et al, 2013, 2014). Various studies have shown that Chinese individuals with developmental dyslexia exhibit visual deficits (Chung et al, 2008; Wang et al, 2010; Meng et al, 2011; Qian and Bi, 2014), and visual function training for dyslexics can improve their reading-related skills (Meng et al, 2014; Wang et al, 2014; Qian and Bi, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…A recent intervention study found visual perceptual training significantly decreased the discrimination threshold of visual texture discrimination task (TDT) for Chinese DD. Meanwhile, DD who accepted training exhibited significant and long-lasting enhancement in reading fluency ( Meng et al, 2014 ). However, this study focused on training of general visual perception.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these studies involving perceptual (eg. auditory [ 11 , 13 , 22 ], vision [ 42 43 ]) or cognitive (eg. memory [ 21 , 30 32 ], attention [ 17 , 32 ]) learning in children, direct comparison between perceptual and cognitive training on phonological and literacy skills, or even on untrained auditory and cognitive skills, has not previously been attempted.…”
Section: Introductionmentioning
confidence: 99%